Occult fractures detected on radiographs in young children with a concern for abusive head trauma - Popelova, Eliska; Holubova, Zuzana; Dvorakova, Marcela; Kyncl, Martin (Biomedical papers, 2024)
Aims. To determine the incidence of children < 2 years old with suspected abusive head trauma, to evaluate usage of dedicated skeletal radiographs and the incidence of clinically occult fractures on dedicated skeletal radiographs. Methods. This is a retrospective single centre study of children < 2 years old with traumatic brain injury, referred to the University Hospital's Social Services Department between December 31, 2012 and December 31, 2020. Clinical and demographic data was retrieved from medical notes and imaging was reviewed by paediatric radiologists. Results. 26 children (17 males), 2 weeks to 21 months of age (median age 3 months) were included. Eleven children (42%) had traumatic history, fourteen children (54%) had one or more bruises, eighteen children (69%) had abnormal neurological findings. 16 children (62%) had dedicated skeletal radiographs, 7 children (27%) had radiographs of part of the skeleton and 3 children (11%) had no skeletal radiographs. 5 out of 16 children (31%) with dedicated skeletal radiographs had a clinically occult fracture. 15 (83%) of clinically occult fractures had high specificity for abuse. Conclusion. The incidence of suspected abusive head trauma in children < 2 years old is low. Clinically occult fractures were detected in one third of children with dedicated skeletal radiographs. The majority of these fractures have high specificity for abuse. Dedicated skeletal imaging is not performed in more than one third of the children and hence fractures may be missed. Efforts should be taken to increase awareness of child abuse imaging protocols.
Keywords: children; abusive head trauma; non-accidental injury; abuse; imaging; fracture